Pengaruh Bacaan (Qira’ah) Al-Qur’an dalam Pembentukan Hukum Islam - Muspira Muspira; Askari Zakariah; Novita Novita (Al Fuadiy Jurnal Hukum Keluarga Islam, 2023)
The Qur'an is the source and pillar of the Islamic religion, in which there are various rules that will not change with changes in time and place. The Qur'an also contains global laws and an explanation of the correct faith, apart from being a proof for the continued existence of the Islamic religion. The Qur'an is also a revelation that comes directly from Allah SWT. There are various instructions and commands from Allah SWT that should be carried out by the people.